Gen Y consumers’ intention to purchase halal food in Malaysia: a PLS-SEM approach - Marmaya, N. H.; Zakaria, Z. A.; Mohd Desa, Mohd Nasir (Emerald Publishing, 2019)
Purpose This study aims to investigate factors that influenced Malaysia’s Gen Y consumers’ behavioral intention to purchase halal food in Malaysia. Design/methodology/approach A quantitative method was adopted in this study and responses were obtained from 110 Gen Y consumers in Malaysia. Findings Using partial least squares structural equation modeling (PLS-SEM), the results showed that subjective norms and perceived behavioral control influenced behavioral intention among Gen Y consumers to purchase halal food, while attitude did not play a significant role in the purchase of halal food products among Gen Y consumers. Research limitations/implications This study adopts a cross-sectional research design and examines the opinions of consumers at only one point in time. Future research also may look upon halal awareness toward other products in a broader geographical area and in other different culture. Longitudinal research design and a bigger sample size should be conducted in future to obtain better results. Practical implications The result of the study would serve as a reference to Malaysian Statutory bodies and food industry on the current intention of Malaysian Gen Y toward halal food. Originality/value Limited researchers have studied Gen Y consumers’ intention to purchase halal food products.